Wetting a Superomniphobic Porous System - Cerda-Villablanca, E (Royal Society of Chemistry, 2019)
While important research has been focused on developing surfaces that do not wet, some textures with high-wetting resistance are familiar in other applications in which the opposite is needed. A multivalued surface, common in most fabrics or meshes, allows the invading gas-liquid interface to support relatively high imposed pressures and plays a key role in producing topographic elements that avoid wetting. Here we study experimentally and theoretically the critical pressure needed to move a liquid through a network of pores and show that, for small aperture size, wetting and leaking are typical first-order transitions, with a singular behavior at the omniphobic/omniphilic limit (θc = π/2). © 2019 The Royal Society of Chemistry.